Analysis of Chemical Properties of Fermented Milk Beverages Containing Probiotics and Influence on Enamel Demineralization: An in Vitro Study - Dayse Andrade Romão; Ingrid Nazaré Araújo de Oliveira Santos; Letícia Ramalho Paes; Maria Rakel de Cerqueira Santos; Gessica Brito Lima Caju; Valdeci Elias dos Santos Júnior; Rafaela Andrade de Vasconcelos; Raphaela Farias Rodrigues; Douglas Ferreira da Silva (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the properties of fermented milk beverages containing probiotics and their potential demineralization on enamel after consumption. Material and Methods: Seven fermented milks were analyzed by titratable acidity and pH, and five were considered for erosive cycling. The beverages' calcium (Ca) and Phosphorus (P) were measured. For measurement of potential erosive, bovine dental enamel blocks (n=8) were individually treated (2 min - 4x/day for five days) with 1% citric acid solution pH 3.5 (control) and strawberry, grape, traditional, and orange fermented milk beverages. At treatment intervals, the blocks were immersed in artificial saliva (1h). The samples were evaluated by profilometry and scanning electron microscopy (SEM) at the end of cycling. The results were submitted to ANOVA and 5% Tukey tests. Results: For titratable acidity, the traditional flavor had the lowest value, 3.36 ± 0.46mmoles, and the grape flavor had the highest value, 10.7 ± 0.1mmoles. The lowest pH value was the strawberry flavor at 3.61 ± 0.07, and the highest was the orange flavor at 4.10 ± 0.07. The orange flavor showed the highest values of Ca (48.19%) and P (9.69%). The fermented milk beverages promoted surface loss; however, citric acid promoted higher values. Conclusion: Fermented milk is an acidic beverage with variations in inorganic components. Their erosive potential is lower compared with citric acid.